FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENERAPAN KOMUNIKASI TERAPEUTIK OLEH PERAWAT PADA PASIEN DI RUANG RAWAT INAP RUMAH SAKIT UMUM DAERAH RADEN MATTAHER JAMBI - Dwi Handayani; Armina Armina (Jurnal Akademika Baiturrahim Jambi, 2017)
Background : From the preliminary study it was found that many nurses did not carry out therapeutic communication properly in accordance with the procedure. The purpose of this study is to obtain a description of the application of therapeutic communication and the knowledge of the application of therapeutic communication by the nurse and to know the factors related to the application of therapeutic communication by the nurses in the patient in the inpatient ward of Raden Mattaher General Hospital in Jambi in 2016. Method :  This research was conducted at General Hospital of Raden Mattaher Jambi about Factors Associated With Application Of Therapeutic Communication By Nurse In Patient In The Inpatient Room of Raden Mattaher General Hospital Jambi from 27 February to 4 March 2016 with respondents 72 people The study design was cross sectional. Result : From the research, the high therapeutic communication is not good. From the result of statistical test by using chi-square analysis with P <0,05, there is a correlation between the application of therapeutic communication with education, work period, education, attitude and gender. Efforts can be made to improve the application of good therapeutic communication can be done by improving higher education, increasing nurse knowledge about therapeutic communication, improvement of work period, nurse can do good attitude in applying therapeutic communication and nurse woman can apply therapeutic communication with Both in the patient.